Review of Adulterated Herbal Products and Supplements and Methods of Analysis - Eureka Qurrotul Ainiyah; Supandi Supandi; Vivi Anggia (UIN Syarif Hidayatullah Jakarta, 2021)
Herbal products and supplements are widely used for primary health care. Many reports of drugs added to these products, such as weight-loss supplements, analgesic herbal products, and erectile dysfunction supplements. This study aims to find out products that are often mixed with drugs and effective methods used for their analysis. The method used in this research is a systematic review. The resources were retrieved through searching the keywords related to the world adulterated herbal products and supplements in the available databases and search engines including Science Direct, PubMed, Springerlink, and Google Scholar. Based on PRISMA flow diagram, a systematic review showed that sibutramine HCl, sildenafil citrate, dexamethasone, and sodium diclofenac are most commonly found in the herbal and supplement products and the ESI-MS method is an effective method for their analysis.